2015
DOI: 10.1515/msr-2015-0023
|View full text |Cite
|
Sign up to set email alerts
|

Ionization Impact on the Air Cleaning Efficiency in the Interior

Abstract: The paper deals with ionization impact on efficient cleaning of air in a measuring chamber which has been cleaned and closed against any outer impacts (e.g. impurities, dust from another room, human odours). Smoking has an impact on the number of positive and negative ions including the concentration of particulate matter PM 10 . We investigated the ion concentration according to the presence of cigarette smoke in the room and according to the change of lit cigarette distance from the supply of ionized air. Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 26 publications
(27 reference statements)
0
16
0
Order By: Relevance
“…PM concentration was reduced by up to two orders of magnitude after 2 hours of treatment by NAI generator in an unoccupied office room (50 m 3 ) [ 144 ]. Many other similar reports showed the high efficiency of NAIs in PM removal ( Table 3 ; [ 138 , 140 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 ]). Evidence showed that many factors might affect PM reducing efficiency by NAIs ( Table 3 ; [ 34 , 139 , 150 , 153 ]).…”
Section: The Release Of Negative Air Ions As An Efficient Way To Rmentioning
confidence: 73%
See 1 more Smart Citation
“…PM concentration was reduced by up to two orders of magnitude after 2 hours of treatment by NAI generator in an unoccupied office room (50 m 3 ) [ 144 ]. Many other similar reports showed the high efficiency of NAIs in PM removal ( Table 3 ; [ 138 , 140 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 ]). Evidence showed that many factors might affect PM reducing efficiency by NAIs ( Table 3 ; [ 34 , 139 , 150 , 153 ]).…”
Section: The Release Of Negative Air Ions As An Efficient Way To Rmentioning
confidence: 73%
“…Many other similar reports showed the high efficiency of NAIs in PM removal ( Table 3 ; [ 138 , 140 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 ]). Evidence showed that many factors might affect PM reducing efficiency by NAIs ( Table 3 ; [ 34 , 139 , 150 , 153 ]). For example, PM removal rate was related to particle concentrations, particle sizes, and the ventilation conditions and a model was raised to compute their relationship [ 139 ].…”
Section: The Release Of Negative Air Ions As An Efficient Way To Rmentioning
confidence: 73%
“…We have obtained a mathematical model for determining the dynamic coefficient, which characterizes the influence of vibrations in the technological system on the value of the cut-off layer when peripheral grinding [9,14]:…”
Section: Methodology Of Researchmentioning
confidence: 99%
“…American experience, resulting from the university innovative entrepreneurship [17,20,44], gives some practical guidelines which can be used on a large scale. The same approach can be found in the aspect of the organization culture impact on innovations [21,22,45,46]. Some companies innovate towards sustainability to improve their socio-environmental and economic performance [2].…”
Section: Literature Reviewmentioning
confidence: 99%